FACS-purified myoblasts producing controlled VEGF levels induce safe and stable angiogenesis in chronic hind limb ischemia - Wolff, Thomas (Blackwell Publishing Ltd, 2012)
We recently developed a method to control the in vivo distribution of vascular endothelial growth factor (VEGF) by high throughput Fluorescence-Activated Cell Sorting (FACS) purification of transduced progenitors such that they homogeneously express specific VEGF levels. Here we investigated the long-term safety of this method in chronic hind limb ischemia in nude rats. Primary myoblasts were transduced to co-express rat VEGF-A(164) (rVEGF) and truncated ratCD8a, the latter serving as a FACS-quantifiable surface marker. Based on the CD8 fluorescence of a reference clonal population, which expressed the desired VEGF level, cells producing similar VEGF levels were sorted from the primary population, which contained cells with very heterogeneous VEGF levels. One week after ischemia induction, 12 × 10(6) cells were implanted in the thigh muscles. Unsorted myoblasts caused angioma-like structures, whereas purified cells only induced normal capillaries that were stable after 3 months. Vessel density was doubled in engrafted areas, but only approximately 0.1% of muscle volume showed cell engraftment, explaining why no increase in total blood flow was observed. In conclusion, the use of FACS-purified myoblasts granted the cell-by-cell control of VEGF expression levels, which ensured long-term safety in a model of chronic ischemia. Based on these results, the total number of implanted cells required to achieve efficacy will need to be determined before a clinical application.